2018
DOI: 10.1097/01.aoa.0000530010.53227.35
|View full text |Cite
|
Sign up to set email alerts
|

Cesarean Delivery in the Second Stage of Labor and the Risk of Subsequent Premature Birth

Abstract: (Am J Obstet Gynecol. 2017;217(1):63.e1–63.e10) Cesarean delivery rates are on the rise in the United States, in part because of the increased use of cesarean delivery rather than forceps and vacuum deliveries for fetal distress and arrest disorders in the second stage of labor. However, cesarean delivery in the second stage of labor can be risky due to the difficulty of delivering a deeply impacted fetal head. Cohort studies have shown increased risk of extensions of the uterine incision, bladder in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(51 citation statements)
references
References 0 publications
4
47
0
Order By: Relevance
“…Also in agreement with Wood et al 20 we found no increased risk of SPTB in pregnancies subsequent to instrumental deliveries.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Also in agreement with Wood et al 20 we found no increased risk of SPTB in pregnancies subsequent to instrumental deliveries.…”
Section: Discussionsupporting
confidence: 93%
“…The same comparison in our study showed a significantly increased rate of SPTB, but the OR of 2.2 (95% CI 1.3-3.8, P = 0.003) was lower. Our results were more comparable with those found by Wood et al 20 They showed a relative risk of 1.57 (95% CI 1.43-1.73) of having a SPTB <37 weeks among women who had a fully dilated CS.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations